Use of the Social Security Administration Death Master File for ascertainment of mortality status - Whitcomb Brian W; Schisterman Enrique F (Population Health Metrics, 2004)
Abstract Objectives Internet sources that use the Social Security Administration's (SSA) Death Master File have demonstrated high sensitivity among males for detection of mortality status in comparisons to the National Death Index, but the sensitivity has not been investigated for other demographic groups. Methods The authors used the SSA Death Master File to determine the mortality status of 374 decedents from the ongoing Patient Outcomes Study at Cedars-Sinai Medical Center whose deaths were confirmed by physicians using hospital records. Results Decedents identified by the SSA Death Master File were significantly older than those not identified. Foreign-born decedents were significantly less likely to be identified as dead than American-born decedents. Gender and marital status were not significant factors for identification by the SSA Death Master File. Conclusion The results of this study suggest that Internet sources may be used as an inexpensive and effective tool for determination of mortality status. However, among certain populations use of these databases alone may provide incomplete information.